The impact of rewards and motivation on job satisfaction: a comparative study between lembaga air Perak (lap) and bekalan air Selangor (syabas) - Khalid, Khalizani; Mat Salim, Hanisah; Loke, Siew Phaik (2011)
This study aimed to examine the impacts of rewards and motivation on job satisfaction between Lembaga Air Perak (LAP) and Syarikat Bekalan Air Selangor (SYABAS) using Perceived Amount of Rewards, WPI and JSS models. A total of 689 employees from both sectors participated in this study. Regression analysis was conducted to test the relationship between rewards, motivation and job satisfaction, while gap analysis was utilized to determine the significant differences on the level of rewards, motivation and job satisfaction between both sectors. The findings indicated that (1) rewards have a positive significant influenced on motivation; (2) motivation significantly positively influenced employees' job satisfaction and (3) rewards have a positive significantly influenced on job satisfaction. The t-test result revealed that public water utility organization showed significantly higher on the levels of rewards, motivation and job satisfaction.